Cello concertos [compact disc] - Isserlis, Steven, 1958-; Isserlis, Steven, 1958-; Haydn, Joseph, 1732-1809; Mozart, Wolfgang Amadeus, 1756-1791; Bach, Carl Philipp Emanuel, 1714-1788; Haydn, Joseph, 1732-1809; Boccherini, Luigi, 1743-1805 (Hyperion, 2017)
Steven Isserlis presents Haydn's two cello concertos, the most accomplished contributions to the instrument's burgeoning repertoire written in the eighteenth century, along with works by Mozart, C.P.E. Bach, and Boccherini.